A chromosome-level genome assembly of Mylabris sibirica Fischer von Waldheim, 1823 (Coleoptera, Meloidae) - Chenhui Shen; Guofeng Yang; Min Tang; Xiaofei Li; Li Zhu; Wei Li; Lin Jin; Pan Deng; Huanhuan Zhang; Qing Zhai; Gang Wu; Xiaohong Yan (Scientific Data)
Abstract Mylabris sibirica is a hypermetamorphic insect that primarily feeds on oilseed rape during the adult stage. However, the limited availability of genomic resources hinders our understanding of the gene function, medical use, and ecological adaptation in M. sibirica. Here, a high-quality chromosome-level genome of M. sibirica was generated by PacBio, Illumina, and Hi-C technologies. Its genome size was 138.45 Mb, with a scaffold N50 of 13.84 Mb and 99.85% (138.25 Mb) of the assembly anchors onto 10 pseudo-chromosomes. BUSCO analysis showed this genome assembly had a high-level completeness of 100% (n = 1,367), containing 1,358 (99.4%) single-copy BUSCOs and 8 (0.6%) duplicated BUSCOs. In addition, a total of 11,687 protein-coding genes and 35.46% (49.10 Mb) repetitive elements were identified. The high-quality genome assembly offers valuable genomic resources for exploring gene function, medical use, and ecology.